DAMPAK PENERIMAAN KREDIT TERHADAP PENDAPATAN PEDAGANG KECIL DI PASAR LIMA PULUH KOTA PEKANBARU - Latifah Asni; Henny Indrawati; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine: (1) Impact of Credit Acceptance Against Revenue Small Traders (2) What percentage of Credit Acceptance Impact Against Small Traders In The Market Revenue Fifty Pekanbaru. This research was conducted in the Market Fifty Pekanbaru City in January - completed. The method used is descriptive quantitative method. The population in this study are traders who sell at the Market Fifty Pekanbaru City totaled 229 people, and sampled from the population amounted to 31 respondents based on predefined criteria. Sampling by purposive sampling. Data were collected through questionnaires and interviews. The researchers used a simple linear regression significant level of 5%. Based on survey results revealed that the acceptance of credit impact on the income of small traders. It is based on analysis using SPSS hashish, partial calculations showed the t (4.673> t table (2.045) and the significance of 0.000 <alpha (0.05). So can disimpulakan that there are a considerable impact on the acceptance of partial credit against the income of small traders in market fifty city of Pekanbaru. the amount of contribution or donation acceptance credit acceptance credit against income traders as shown by the R Square of 0.430. that is that the contribution of the revenue impact of credit on the income trader is at 43% and the balance of 57% is not addressed in other studies.Keywords : Impact, Credit Receipts, Income